1979
DOI: 10.1073/pnas.76.7.3518
|View full text |Cite
|
Sign up to set email alerts
|

Human glomerular visceral epithelial cells synthesize a basal lamina collagen in vitro.

Abstract: Isolated human glomeruli were digested with purified bacterial collagenase yielding epithelial cells. These cells grew to saturation density and did not become multilayered. They were identified as visceral glomerular epithelial cells by their morphologic appearance by phase and electron microscopy and by the presence of surface receptors for C3b. Neither Factor VIII antigen nor Fc receptors were observed. The glomerular epithelial cells synthesized a collagenous protein that was antigenically similar to human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 41 publications
0
22
1
Order By: Relevance
“…Previous biosynthetic studies of collagen by glomerular cells have evidenced the pres ence in the culture medium of collagenous chain which exhibited an electrophoretic mobility comparable to that of the pro-a, (IV) and pro-a2 (IV) chains characterized in this study [Scheinman et al, 1978], Killen and Striker [1979] have recently shown that glomerular epithelial cells synthesize and secrete in the culture medium a collagenous protein which can be precipitated with an antibody against GBM, which has the same electrophoretic properties and the same amino acid ratios as the pro-a, (IV) and proa 2 (IV) collagen chains analyzed here [Killen and Striker, 1979], The predominant prol ine-labeled protein synthesized by their glo merular epithelial cells was fibronectin which was also evidenced in our cultures of epithelial and mesangial cells.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous biosynthetic studies of collagen by glomerular cells have evidenced the pres ence in the culture medium of collagenous chain which exhibited an electrophoretic mobility comparable to that of the pro-a, (IV) and pro-a2 (IV) chains characterized in this study [Scheinman et al, 1978], Killen and Striker [1979] have recently shown that glomerular epithelial cells synthesize and secrete in the culture medium a collagenous protein which can be precipitated with an antibody against GBM, which has the same electrophoretic properties and the same amino acid ratios as the pro-a, (IV) and proa 2 (IV) collagen chains analyzed here [Killen and Striker, 1979], The predominant prol ine-labeled protein synthesized by their glo merular epithelial cells was fibronectin which was also evidenced in our cultures of epithelial and mesangial cells.…”
Section: Discussionmentioning
confidence: 76%
“…Alterations of the extracellular matrix of the glomeruli occur in various conditions [Churg and Grishman, 1976], Connective tissue proteins such as collagens, fibronectin and laminin have been localized in glomer uli by immunohistochemical methods both at the light and electron microscope level [Stenman and Vaheri, 1978;Scheinman et al 1980a, b;Madri et al, 1980], The cells responsible for the synthesis of these pro teins have not been unequivocally defined. The recent isolation of homogeneous popu lation of glomerular epithelial and mesan gial cells has allowed the study of some of their metabolic activities [Foidart et al, 1979[Foidart et al, ,1980a, In particular, the biosynthesis of GBM peptides [Scheinman et al, 1978;Killen and Striker, 1979;Foidart et al, 1980b, c] or of prostaglandins by these cells [Sraer et al, 1980] have been previously investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Such an observation is consis tent with reports of two genetically distinct collagen polypeptides in lens capsule [10,11] and it is of interest that glomerular epithelial cells in culture also synthesise collagenous polypeptides which migrate as a doublet on polyacrylamide gels [12]. Further studies are in progress on the characterization of the rat GBM collagen precursors but it can be con cluded that the collagens of lens capsule and GBM are probably assembled by the same basic mechanisms.…”
Section: Resultsmentioning
confidence: 54%
“…(1) Isolation and preparation of glomerular cells was performed isolating glomeruli from rat kidneys after the principle of Krakower and Greenspon [6] and Lubec [7] and the glomerular cells were isolated from intact glo meruli after the method of Killen and Striker [8], 2.5xIO7 cells were applied in the experiments.…”
Section: Methodsmentioning
confidence: 99%